Chasing real-time interaction in new media: towards a new theoretical approach and definition. Issue 3 (3rd July 2017) - Sora, Carles; Jordà, Sergi; Codina, Lluís
ABSTRACT: 'Real-Time' is one of the most frequent concepts used referring to digital media. Despite it is commonly related to immediate feedback, it is not clear when it happens and what its characteristics are, especially in current digital interfaces. Although real-time has been written about very extensively in the context of Human Computer Interaction and Computational Systems, there are few studies evaluating the key features of real-time interaction in other domains. This article attempts to address this situation by proposing a new approach to the concept of real-time interaction driving the analysis of this topic into paradigmatic cases studies in new media, video games and digital artworks. This new analysis reveals several specific facets that allow us to identify new factors in the understanding of this fuzzy concept. Finally, the article proposes a new definition of 'real-time interaction' based on the findings in the context of new media practices.